Polska w Układzie Warszawskim – realizacja zobowiązań: Poland in the Warsaw Pact – implementation of commitments - Kajetanowicz, Jerzy (Przegląd Wschodnioeuropejski, 2021)
The Warsaw Pact created in 1955 for almost 40 years played an important role in maintaining international security. Poland, due to its military and economic potential, was the second largest member of this alliance. For this reason, it sought to ensure a real impact on its functioning, which was reflected in its active participation in the implementation of the provisions of the agreement on the political, military and economic levels. Poland’s political activity was expressed in numerous initiatives to ensure peace and in active participation in international cooperation. Military commitments were implemented through the preparation of modern operational troops, from which a strategic and operational union was created in the form of a Maritime Front, ready to act as part of the United Armed Forces of the Warsaw Pact throughout the period of membership in this alliance. In turn, economic cooperation was manifested in close cooperation in the production of various weapon systems and military equipment, as well as the development of defense infrastructure for both own needs and allies.